Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

Solve 2(x-6)+7x = 5-3(x-2)

Sagot :

[tex]2(x-6)+7x=5-3(x-2)[/tex]

To solve x, let's eliminate the parenthesis first by multiplying 2 and -3 to it.

[tex]2x-12+7x=5-3x+6[/tex]

Next, let's combine all like terms on either side. We will move -3x to the left side of the equation and -12 to the right side of the equation. Note that when a term crosses the equal symbol, the sign reverses. From -3x to +3x and from -12 to +12.

[tex]2x+7x+3x=5+6+12[/tex]

Next, add the terms on both sides.

[tex]12x=23[/tex]

Lastly, divide both sides by 12 to isolate x.

[tex]\begin{gathered} \frac{12x}{12}=\frac{23}{12} \\ x=\frac{23}{12} \end{gathered}[/tex]

The value of x is 23/12.

Let's check if this is right by substituting the value of x to the equation.

[tex]\begin{gathered} 2(\frac{23}{12}-6)+7(\frac{23}{12})=5-3(\frac{23}{12}-2) \\ 2(-\frac{49}{12})+\frac{161}{12}=5-3(-\frac{1}{12}) \\ -\frac{98}{12}+\frac{161}{12}=5+\frac{3}{12} \\ \frac{63}{12}=\frac{63}{12} \\ \frac{21}{4}=\frac{21}{4} \end{gathered}[/tex]

Since we got the same 21/4 on both sides of the equation, our x value 23/12 is correct.